Integrating robot journalism into newsrooms: perspectives, opportunities, and challenges among Egyptian journalists - Okela, Abdelmohsen Hamed; Arandas, Mohammed Fadel; Danso, Samuel; Ziani, Abdulkrim; Kasmi, Sami; Al-Derai, Hamad (Frontiers in Communication, 2026)
This study explored how Egyptian journalists perceive the opportunities and challenges of robot journalism and its effect on newsroom operations. Guided by Roger Fidler’s Mediamorphosis Theory and in-depth interviews with journalists, the study reveals that artificial intelligence improves efficiency, data processing and investigative reporting. The participants cited ethical responsibility, employment stability, and cultural appropriateness as areas of concern. The findings highlight how Egyptian reporters are seeking a moderate solution and automation, which does not compromise professional judgment or public confidence. The study reveals that the adoption of robot journalism needs to be done responsibly and contextually to facilitate innovation in Egypt’s rapidly evolving media landscape.